Biodegradation Properties Of Az31 Magnesium Alloy Coated by Dicalcium Phosphate Dihydrate - Pastorek, Filip; Omasta, Miroslav; Bukovinova, Lenka; Dolezal, Pavel; Hadzima, Branislav (Communications - Scientific letters of the University of Zilina, 2014)
Biodegradation properties of magnesium and its alloys that can be used for implants are not satisfactory and cause serious problems. These problems can be solved by biodegradable surface coatings. Evaluation of biodegradation process of Mg-3Al-1Zn alloy surfaces after grinding and grinding followed by potential controlled electrodeposition of dicalcium phosphate dihydrate (DCPD) was investigated by electrochemical impedance spectroscopy measurements in this study. The potentiostatic electrodeposition treatment process was performed in water solution of Ca(NO3)2.4H2O, NH4H2PO4 and H2O2. The corrosion process on treated and nontreated samples after various exposure times was evaluated in 0.9% NaCl solution simulating body fluid environment at 37 °C.